A single centre, real world experience of T-DM1 in the treatment of HER2-positive metastatic breast cancer patients in India - Vasini, Vindhya; Vamsy , Mohana; Dayal, Monal; Shinkar, Pawan (Journal of Applied Pharmaceutical Research, 2024)
Background: HER2 (Human Epidermal Growth Receptor 2) positive breast cancer is an aggressive subtype. Treatment for patients with HER2-positive breast cancer has advanced significantly over time with the introduction of targeted therapies like trastuzumab, pertuzumab, lapatinib, trastuzumab emtansine, trastuzumab, deruxtecan, and tucatinib. In a lower-middle-income nation, accessibility is still problematic for any newer therapy. This study aimed to describe the safety and practical effectiveness of the first T-DM1 biosimilar in India for treating patients with HER2-positive mBC. Methodology: This is a retrospective, observational, single-center study of patients with HER2-positive metastatic breast cancer treated with T-DM1 biosimilar. The study involved 16 mBC patients. The primary goal was to assess T-DM1's effectiveness regarding PFS and ORR, with safety and OS as the secondary goals. Results: The ORR was observed to be 81.3%. One (6.29%) of the patients achieved CR, while 3 patients (18.8%) are on stable disease, and 12 patients (75 %) achieved PR. The major adverse events reported among study patients were thrombocytopenia (31.25%) and anemia (31.25%), followed by neutropenia, hyperglycemia, and fatigue in 12.5 % of cases. Grade 3 thrombocytopenia was seen in 2 patients, and grade 3-4 fatigue was observed in 1 patient. Median PFS was nearly six months, and OS data is available for only 25% of patients; the rest continue the therapy. Conclusion: This retrospective observational study offers significant information about the safety and efficacy of T-DM1 biosimilar in treating HER2 positive mBC.